The exact performance evaluation for modern wireless communications in Nakagami fading - Pongsatorn Sedtheetorn (2018)
This paper presents a theoretical analysis on the system performance indicators, in terms of bit error rate and spectral efficiency, for modern wireless communication systems in the general case of fading environment, namely Nakagami fading. Based on moment generating function technique, we derive the cumulative probability functions of signal-to-interference-plus-noise-ratio. This leads us to propose new exact expressions for bit error rate and spectral efficiency in Nakagami fading. Validated with Monte Carlo simulation, the proposed expressions benefit us a low-numerical complexity approach to compute the exact performances of the systems. © 2013 IEEE.